How Neutrality Lost its Appeal as a Political Strategy: Sweden and Finland’s Accesion to NATO - Kaynak, Akif Bahadır (Journal of Applied And Theoretical Social Sciences, 2023)
NATO is about to embrace two Scandinavian countries as new members, even though Sweden and Finland opted for neutrality during the Cold War. In the political turmoil of the second half of 20th century, those two countries preferred to stay on the sidelines. The struggle between two poles of global politics raged on, yet even after more than three decades since the collapse of Soviet Union, they choose not to commit to the Western alliance. After a period during which existence of NATO was questioned, it is imperative to explain how once again the alliance attracts newer members to its fold. Evidently, Russia-Ukraine war was the trigger behind the change in strategies but the question how this conflict is different than has other Cold War engagement remains. This paper investigates how NATO membership became the optimal strategy for previously non-aligned countries in Europe even after a bipolar world order faded away. A game theory approach outlining the choices and payoffs for Russia versus Sweden and Finland will be used to understand the changing strategies for all actors.